PENERAPAN HIDROPONIK TANAMAN KANGKUNG ORGANIK DI KELURAHAN LOKOBOKO KECAMATAN NDONA - Charly Mutiara; Diana Segu; Philipus Nerius Supardi (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
Community service through the Independent Community Service Program with the theme "Application of Organic Kale Plant Hydroponics" has been carried out. The series of activities carried out were exploring problems, training in making fertilizers or nutrients for hydroponic plants, hydroponic seeding of kale seeds and planting water spinach seeds hydroponically as well as applying organic fertilizers. The parties involved in this activity are students, village officials and the community in Lokoboko Village. The results obtained from this activity were examples of hydroponic vegetable cultivation with an organic system and high enthusiasm from all parties involved to implement it. From these results, it is suggested that this hydroponic method can be applied in the yards of the Lokoboko village community.